1988
DOI: 10.2106/00004623-198870010-00014
|View full text |Cite
|
Sign up to set email alerts
|

Limits of movement in the human knee. Effect of sectioning the posterior cruciate ligament and posterolateral structures.

Abstract: We applied specific forces and moments to the knees of fifteen whole lower limbs of cadavera and measured, with a six degrees-of-freedom electrogoniometer, the position of the tibia at which the ligaments and the geometry of the joint limited motion. The limits were determined for anterior and posterior tibial translation, internal and external rotation, and varus and valgus angulation from zero to 90 degrees of flexion. The limits were measured in the intact knee and then the changes that occurred with remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
419
1
10

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 615 publications
(447 citation statements)
references
References 22 publications
17
419
1
10
Order By: Relevance
“…In comparing laxity between both compartments, the constraint was stronger in the medial compartment because the PCL was attached to the medial side of the femur. In addition, external rotation of the tibia reportedly is limited by the posterolateral structure [8,9]. We were not able to evaluate isolate function of the posterolateral structure in our study, but it would have some influence on stability at lateral compartment.…”
Section: Discussionmentioning
confidence: 88%
“…In comparing laxity between both compartments, the constraint was stronger in the medial compartment because the PCL was attached to the medial side of the femur. In addition, external rotation of the tibia reportedly is limited by the posterolateral structure [8,9]. We were not able to evaluate isolate function of the posterolateral structure in our study, but it would have some influence on stability at lateral compartment.…”
Section: Discussionmentioning
confidence: 88%
“…1,2,10 These structures act as primary stabilizers to prevent abnormal varus and tibial external rotation, while serving an important secondary role to the cruciate ligaments in preventing anterior and posterior translation of the knee. 1,2 The dynamic function of individual posterolateral knee structures in the goat and their role in the prevention of abnormal joint motion has not yet been established in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] It has been well documented that the fibular collateral ligament, popliteus tendon, and popliteofibular ligament are the primary stabilizers to abnormal varus, external rotation, and coupled posterolateral rotation for the human knee. 1,2,10 However, in vivo studies on animal models, other than the rabbit, 11 demonstrating the natural history of injuries to the posterolateral aspect of the knee have not yet been performed. A recent anatomic study revealed that the rabbit knee has many similarities to the human knee.…”
Section: Introductionmentioning
confidence: 99%
“…In the human knee, the most important posterolateral knee structures, based on biomechanical studies, to preventing abnormal joint motion are the FCL, popliteus tendon, and PFL [4,5,24]. These structures act as the primary stabilizers to preventing abnormal varus and tibia1 external rotation motion, and serve an important secondary role to the cruciate ligaments in preventing anterior and posterior translation of the knee [4,5]. The role of individual posterolateral knee structures on preventing abnormal joint motion or their dynamic function in the rabbit knee has not been established in the literature.…”
Section: Discussionmentioning
confidence: 99%